Construção e avaliação de vacinas de toxina α recombi-nante de Clostridium perfringens A - Santos, João Rodrigo Gil de Los (2007)
Avian Necrotic Enteritis (NE) is an acute enterotoxaemia caused by Clostridium perfringens A and C. The control of the disease is based on antibiotics added to animal feed. The ban of this practice by consumer markets, considered the biggest challenge to industrial aviculture, demanded the adoption of other alternatives for its control, among others, immunization with recombinant vaccines. The aim of this work was to produce and evaluate C. perfringens recombinant α toxin (rAT) vaccines adjuvanted with either Al(OH)3 (rAT+Al(OH)3 or recombinant B subunit of the heat-labile enterotoxin of Escherichia coli (rLTB) (rAT+rLTB), and a chimeric protein containing the α toxin fused to rLTB (rLTB-AT). The rAT+Al(OH)3 was innocuous and protected mice against a challenge with native α toxin (sT), and it was immunogenic and did not affect productivity parameters in broilers. The rAT+rLTB showed a dose-protection relationship in mice, while rLTB-AT did not protect mice against sT challenge. The rAT could be an alternative for controlling NE.